University Presidents See Growing Role for Scholarship of Engagement - Guy Bailey; William V. Muse; Lee T. Todd; David Wilson; David A. Francko (The University of Alabama, 2022)
Keynote panel from the 2012 National Outreach Scholarship Consortium Conference